Blocking Placental Class G Immunoglobulin Transfer Prevents NMDA Receptor Antibody Effects in Newborn Mice. Issue 6 (November 2021) - García-Serra, Anna; Radosevic, Marija; Ríos, José; Aguilar, Esther; Maudes, Estibaliz; Landa, Jon; Sabater, Lidia; Martinez-Hernandez, Eugenia; Planagumà, Jesús; Dalmau, Josep
Abstract : Background and Objectives: To determine in a mouse model whether neonatal Fc receptor (FcRn) blockade prevents the placental transfer of class G immunoglobulin (IgG) derived from patients with anti-NMDA receptor (NMDAR) encephalitis and their pathogenic effects on the fetuses and offspring. Methods: Pregnant C57BL/6J mice were administered via tail vein FcRn antibody (FcRn-ab) or saline solution 6 hours before administration of patients' or controls' IgG on days 14, 15, and 16 of gestation. Three experimental groups were established: mice receiving controls' IgG, patients' IgG, or patients' IgG along with pretreatment with FcRn-ab. Immunohistochemical staining, confocal microscopy, hippocampal long-term potentiation, and standardized developmental and behavioral tasks were used to assess the efficacy of treatment with FcRn-ab. Results: In pregnant mice that received patients' IgG, treatment with FcRn-ab prevented the IgG from reaching the fetal brain, abrogating the decrease of NMDAR clusters and the reduction of cortical plate thickness that were observed in fetuses from untreated pregnant mice. Moreover, among the offspring of mothers that received patients' IgG, those whose mothers were treated with FcRn-ab did not develop the alterations that occurred in offspring of untreated mothers, including impairment in hippocampal plasticity, delay in innate reflexes, and visuospatial memory deficits. Discussion: FcRn blockade prevents placental transfer of IgG from patients with anti-NMDAR encephalitis and abrogates the synaptic and neurodevelopmental alterations caused by patients' antibodies. This model has potential therapeutic implications for other antibody-mediated diseases of the CNS during pregnancy.